The Use of Historical Methods in Analyzing the Urban Structure of Jayapura City - Alfini Baharuddin (BRILIANT: Jurnal Riset dan Konseptual, 2020)
Jayapura City is located at the eastern end of Indonesia and directly borders with neighboring countries, Papua New Guinea (PNG). Geographical conditions vary from Jayapura City is dominated by hills lead to the formation of urban areas are separated. Currently there are two major parts of the city area known as Jayapura and Abepura. The existence of two parts of the city in Jayapura City became one of the interesting things to be studied to determine its relevance to historical factors. Through the historical method approach, the division of developmental stages into some phases was carried out to understand how the pattern of historical development of Jayapura City is. From the discussion by using the historical methods is known that the two parts of the city has existed since the founding of Jayapura City and persisted until today.